A Critical Look at Sustainable Development in the Canadian North - Duerden, Frank (ARCTIC, 1992)
The notion of sustainable development has considerable appeal in northern Canada, a reflection of traditional practices of indigenous populations and the region's experiences with the encroachment of industrial society. The lexicon of "sustainable development" has made the identification of appropriate economic activities a central issue. There is no standard approach to this problem although Weeden (1989) produced a useful framework for evaluation. Analysis of the evolution of the economic geography of the North provides some insights into both the current emphasis on the role of communities in sustainable development strategies and the origin of candidate activities. Review of possible candidate activities suggests that there is perhaps a tendency to confuse renewal with sustainability and that the appropriateness of activities may be called into doubt when viewed from the standpoint of relative energy consumption and global context. Sustenance harvesting is seen as perhaps the most viable sustainable activity, although some assessments of its value may be overstated. Non-renewable resource exploitation is a particular problem, yet the extraction of some non-renewable resources may contribute to a global goal of sustainability. A prerequisite for the development of a rational approach to sustainability lies in establishing the nature of the reciprocal relationship between urban centres and the northern periphery.Key words: sustainable, development, energy, harvesting, indigenous, resource RÉSUMÉ. Le concept de développement durable jouit d’une grande popularité dans le Canada septentrional, ce qui reflète les pratiques traditionnelles des populations autochtones et l’expérience qu’a la région de l’empietement de la société industrielle. Le vocabulaire du développement durable a fait de l’identification des activités économiques appropriées une question centrale. Il n’existe pas d’approche standard à ce problème bien que Weeden (1989) ait produit un cadre utile d’évaluation. Une analyse de l’évolution de la ...